Redesign Web Sekolah Metode User Centered Design - Efendi, Yoyon; Tashid, Tashid; Yenni, Helda; Rio, Unang; Muzawi, Rometdo (Building of Informatics, Technology and Science (BITS), 2021)
The web is indispensable as a medium for school promotions to attract interest and information about schools. This website will be used to make it easier for both teachers, students, and guardians of students. The problem we often face is that the appearance of the website is unattractive and less informative. Starting from unattractive colors, news and information are not updated. It is necessary to redesign the school web to provide an attractive and informative appearance. The method in this research uses User Centered Design (UCD) starting from Plan, Design, Prototype and review. This study aims to produce a website for SMK Negeri 1 Perhentian Raja that is informative and liked by users